Selective and sensitive fluorescent turn‐off chemosensors for Fe3+. (17th September 2012) - Fu, Li; Mei, Jie; Zhang, Ji‐Tao; Liu, Yi; Jiang, Feng‐Lei
ABSTRACT: Two novel chemosensors (2a and 2b) were synthesized by facile condensation of the binding unit (l ‐histidine) and the fluorophores (anthracene and dansyl groups). Both of them displayed high selectivity and sensitivity towards Fe 3+ over other metal ions in aqueous solution. The sensing mechanism was based on the paramagnetic property of Fe 3+ that would lead to fluorescence quenching of the fluorophores when Fe 3+ was bound to the recognition units. The results showed thatl ‐histidine was a good coordination motif for Fe 3+ and both the anthracene and dansyl groups can sensitively report the sensing information. Copyright © 2012 John Wiley & Sons, Ltd.